2018
DOI: 10.1111/jon.12570
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging in Psychiatric Disorders: A Bibliometric Analysis of the 100 Most Highly Cited Articles

Abstract: BACKGROUND AND PURPOSE Extensive research has been conducted to find neuroimaging biomarkers for psychiatric disorders. This study aimed at identifying trends of the 100 most highly cited articles on neuroimaging in primary psychiatric disorders. METHODS The most highly cited original research articles were identified and analyzed, following searches of MEDLINE and Web of Science All Databases. RESULTS The top 100 articles ranked by yearly citation (from 137.5 to 31.1) were published between 1989 and 2017. Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…The brain regions revealed in this study are known to be involved in TRD [7,20]. The insula is particularly involved in emotional identification and in the affective state in response to a stimulus.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The brain regions revealed in this study are known to be involved in TRD [7,20]. The insula is particularly involved in emotional identification and in the affective state in response to a stimulus.…”
Section: Discussionmentioning
confidence: 65%
“…PET is one of the main neuroimaging techniques evaluated in recent psychiatry research [20]. Indeed, PET is usually preferred to SPECT because of better spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…14 The same disparity is observed in the field of brain imaging. A recent bibliometric review found that among the 100 most highly cited neuroimaging studies in psychiatric disorders, only six had a LMIC researcher as first author 16 (China in all cases). In Brazil, only one large neuroimaging study designed to assess various outcomes in terms of psychopathology with published data on youth depression is available.…”
Section: Introductionmentioning
confidence: 99%
“…The brain regions revealed in this study are known to be involved in TRD 7,20 . The insula is particularly involved in emotional identi cation and in the affective state in response to a stimulus.…”
Section: Discussionmentioning
confidence: 70%